From Planet to Profit : The Triple Impact of Green Invesment, Environmental Performance, and Financial Performance - Sahira Pebrianti; Vita Cita Mulyandini (LP2M IAIN Palopo, 2025)
The purpose of this research is to examine the influence of green investment, environmental performance, and profitability on firm value. This study applies a quantitative approach using secondary data obtained from annual reports, PROPER reports, and sustainability reports. A purposive sampling technique was used to determine the sample, resulting in 17 companies with a total of 85 observations. The analytical methods employed include classical assumption testing, multiple linear regression analysis, the coefficient of determination, t-tests, and F-tests, all processed using SPSS version 31. The findings reveal that green investment has a positive and significant effect on firm value, environmental performance has no effect on firm value, and profitability has a positive and significant effect on firm value. Furthermore, simultaneous testing shows that green investment, environmental performance, and profitability collectively exert a significant influence on firm value. These results imply that additional factors may also contribute to firm value, emphasizing the need for companies to consider broader aspects of corporate sustainability. Future research is encouraged to incorporate variables such as carbon emission disclosure, institutional ownership, and corporate social responsibility.